2021
DOI: 10.3390/cells10102742
|View full text |Cite
|
Sign up to set email alerts
|

The Regulatory Activity of Noncoding RNAs in ILCs

Abstract: Innate lymphoid cells (ILCs) are innate lymphocytes playing essential functions in protection against microbial infections and participate in both homeostatic and pathological contexts, including tissue remodeling, cancer, and inflammatory disorders. A number of lineage-defining transcription factors concur to establish transcriptional networks which determine the identity and the activity of the distinct ILC subsets. However, the contribution of other regulatory molecules in controlling ILC development and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 107 publications
(112 reference statements)
0
6
0
Order By: Relevance
“…A vastly unexplored and complex area of investigation is that which assesses the potential role of post-transcriptional regulation in ILC1: ILC3 balance. Emerging reports suggest that ILC functionality can be controlled by miRNA, noncoding RNA, or RNA-binding proteins, as reviewed recently [98][99][100][101][102]. However, in terms of TF regulation, insight is limited to the observation that noncoding RNA IncKdm2b can promote the expression of the TF Zfp292, which is required for intestinal ILC3 maintenance, as evidenced by the impaired SI ILC3 cellularity in LncKdm2b -/mice [101].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A vastly unexplored and complex area of investigation is that which assesses the potential role of post-transcriptional regulation in ILC1: ILC3 balance. Emerging reports suggest that ILC functionality can be controlled by miRNA, noncoding RNA, or RNA-binding proteins, as reviewed recently [98][99][100][101][102]. However, in terms of TF regulation, insight is limited to the observation that noncoding RNA IncKdm2b can promote the expression of the TF Zfp292, which is required for intestinal ILC3 maintenance, as evidenced by the impaired SI ILC3 cellularity in LncKdm2b -/mice [101].…”
Section: Discussionmentioning
confidence: 99%
“…A vastly unexplored and complex area of investigation is that which assesses the potential role of post-transcriptional regulation in ILC1:ILC3 balance. Emerging reports suggest that ILC functionality can be controlled by miRNA, noncoding RNA, or RNA-binding proteins, as reviewed recently [ 98. , 99.…”
Section: Discussionmentioning
confidence: 99%
“…Studies which investigate whether and how cILCs are regulated by factors known to control ILC activity in other tissues and disease states are also required. This may include investigation of cILC regulation by neurotransmitters and neuropeptides ( 1 , 84 ), post-transcriptional regulation by non-coding RNAs ( 85 87 ), and effects of metabolic dysfunction, such as lactic acidosis ( 88 ) - a known indicator of cardiac stress. Further studies which compare functions and transcriptional profiles of cILCs with more widely studied barrier ILC populations would also be useful.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…In recent years, several studies have revealed that mRNA stability affects the function of ILCs ( 21 , 22 ). The first mechanism of mRNA degradation is exonucleolytic degradation, which removes the poly(A) tail (PAT) by exonucleases, such as the carbon catabolite repression 4 (CCR4)-negative on TATA-less (NOT) complex or poly(A)-specific ribonuclease (PARN).…”
Section: Introductionmentioning
confidence: 99%